Asrama Putra Dan Putri Sma Negeri 6 Elar Di Kabupaten Manggarai Timur Dengan Tema Arsitektur Perilaku - Siso, Silvester M.; dede, Petrus Jhon Alfred Depa; Reka, Farida Skolastika (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2023)
Dormitory is a place of lodging intended for members of a group, generally school students. Dormitory is usually a building with rooms that can be occupied by several occupants in each room. The purpose of the research is to design a dormitory building which is equipped with facilities to meet the needs of students and behavioral architecture is a part of providing the required facilities. The method used in this study is in the form of collecting observation data, interviews, evaluating, and observing user behavior as a reference in the analysis of the application of building design. The concept of implementing behavioral architecture in dormitory buildings follows the symbol or symbol of the high school student council such as in the parking lot a hand-shaped pattern is applied. In the library building a book-shaped pattern is applied, at the roundabout a circular pattern is applied like a wrench and in the garden a star-shaped pattern is applied. The application of behavioral architecture is inseparable from the 4 principles of behavioral architecture such as aesthetics of form, being able to communicate with humans and the environment, paying attention to user behavior, and accommodating behavioral activities. So it can be concluded that the dormitory is one of the most important buildings, especially for SMAN 6 Elar and with the application of behavioral architectural design principles, it can be seen in the activity zone processing building, mass composition, as well as the inside and outside appearance of the building adapted to the character of the students. students..